Health Analysis of Bank Syariah Indonesia (BSI): Comparation Before and After The Merger - Amin, Andi Mustika; Nurman; Hasbiah, Siti; Aslam, Annisa Paramaswary; Anugrah, Fira (PT. Maju Malaqbi Makkarana, 2023)
This study aims to determine differences in the soundness level of government owned Islamic banks before and after the merger using the Risk Profile, Good Corporate Governance, Earnings, and Capital methods. This study uses quantitative anda comparative methods with secondary data types in the form of quarterly financial reports obtained from the bank’s official website and www.ojk.co.id. The samples in this research are balance sheets and reports profit and loss of Bank Syariah Mandiri, BNI Syariah, BRI Syariah, and Bank Syariah Indonesia in the 2018-2022 period. Based on the results of research with bro using the RGEC method which consists of Risk Profle with a Non ratio Performing Financing (NPF), and Financing to Deposit Ratio (FDR), Good Corporate Governance with Net Open Position (PDN) ratio, Earnings with gan Return On Asset (ROA) and Capital ratio with the Capital Adequacy Ratio (CAR). The results of the NPF, PDN, ROA, and CAR ratio analysis provide result that there is a significant difference in this ratio before and after the merger. Meanwhile, the FDR ratio shows that there is no difference in the results significant before anda after the merger. Based on research has been carried out, it can be concluded tha Bank Syariah Indonesia is improving after the merger.